A one-component bonding addition type organic silicone adhesive for electronic controller units
By using modified nano-boron nitride and ultra-high functionality cross-linking agents in one-component bonding addition-type silicone adhesives, the problems of insufficient thermal conductivity and poor bonding strength of existing adhesives are solved, and high thermal conductivity is achieved. and high bonding strength.
Patent Information
- Application Number
- CN202411452724.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2044-10-17
AI Technical Summary
The existing single-component bonding addition molded silicone adhesives have insufficient thermal conductivity and poor bonding strength in electronic controller units, so they cannot effectively derive the heat production of electronic controller units.
Modified nano-boron nitride and ultra-high functionality cross-linking agents are used to evenly disperse the modified nano-boron nitride through stirring and dispersion technology, and the ultra-high functionality cross-linking agent is used to improve the mechanical strength and cross-linking properties of the glue. The connection density results in an adhesive with high thermal conductivity and high bonding strength.
The thermal conductivity is between 7.53~7.85W/(m·k), the bonding strength is between 3.1~3.4MPa, the tensile strength is between 6.5~7.3MPa, and the flame retardant grade is V0, which significantly improves the thermal conductivity of the adhesive. performance and bonding strength.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to a single-component bonding addition type organic silicone adhesive for an electronic controller unit, belonging to the technical field of adhesives. Background Art
[0002] One-component bonding and addition type organic silicone adhesive is a widely used thermal insulation material in the electronic and electrical industry. It does not release heat, is non-corrosive, and has a small shrinkage rate when solidified. It is suitable for various thermal sealing and pouring of electronic components to form a thermal insulation system. Especially when used in electronic controller units, one-component bonding and addition type organic silicone adhesive has the advantages of room temperature curing, fast curing, high production efficiency, simple and fast gluing, maintaining elasticity in a wide temperature range, excellent insulation performance, good thermal conductivity, waterproof, moisture-proof, mildew-proof, dust-proof, fixing components, chemical medium resistance, yellowing resistance, and weather aging resistance. However, with the rapid development of the electronic and electrical industry, the power and heat generation of electronic controller units are constantly increasing, and the requirements for the thermal conductivity of one-component bonding addition-type silicone adhesives are getting higher and higher. However, the thermal conductivity of one-component bonding addition-type silicone adhesives is still relatively low. In addition, the inherent bonding performance of addition-type silicone adhesives is poor, and the contact with the electronic controller unit is not strong enough. During long-term use, it also creates great obstacles to the timely and effective removal of the heat generated by the electronic controller unit. Therefore, it is very important to improve the thermal conductivity and bonding strength of one-component bonding addition-type silicone adhesives.
[0003] Chinese patent CN116622243A discloses a method for preparing a one-component addition-type liquid silicone rubber, comprising the following steps: step A, preparing raw materials: including 100 parts of active ingredients as vinyl silicone oil, 5-30 parts of cross-linking agent as hydrogen-containing silicone oil, 0-20 parts of color paste, 0.05-1 parts of platinum catalyst, 1-20 parts of water, 0.01-0.2 parts of organic solvent, 0.5-1 parts of platinum complex, 4-8 parts of ethylene glycol; step B, stirring treatment: adding the raw materials in step A to the reactor, starting the stirrer to stir, stirring for 6-10 minutes; step C, heat treatment: heating the raw materials in step B for heat treatment. The one-component addition-type liquid silicone rubber obtained in this patent does not contain thermal conductive fillers, and it can be inferred that its thermal conductivity will be very poor, and it is not suitable for thermal conductive sealing of electronic controller units.
[0004] Chinese patent CN111154453A discloses a heat-resistant one-component addition-type organic silicone adhesive and a preparation method thereof, wherein the heat-resistant one-component addition-type organic silicone adhesive comprises the following raw materials: vinyl silicone oil, silicone resin, hydrogen-containing silicone oil, heat-resistant additives, fillers, white carbon black, catalysts, inhibitors, and tackifiers. The heat-resistant one-component addition-type organic silicone adhesive prepared by the present invention has moderate viscosity, good construction operability, high tensile strength, excellent bonding performance, can achieve the destruction of the bonding layer, long storage time, and good 300°C hot air aging performance. The one-component addition-type organic silicone adhesive obtained by the patent, although having relatively good heat resistance and relatively good bonding strength, does not have the function of high thermal conductivity, and cannot be used for thermal conductive sealing of electronic controller units.
[0005] From the above, we can see that the current one-component bonding addition type organic silicone adhesives still have problems such as poor bonding performance and insufficient thermal conductivity. The market is in urgent need of one-component bonding addition type organic silicone adhesives for electronic controller units. Therefore, the development of one-component bonding addition type organic silicone adhesives with high bonding strength and excellent thermal conductivity has very practical application value. Summary of the invention
[0006] In view of the deficiencies of the above-mentioned prior art, the present invention provides a one-component bonding addition type organic silicone adhesive for an electronic controller unit to achieve the following invention objectives: to prepare a one-component bonding addition type organic silicone adhesive with high bonding strength and excellent thermal conductivity.
[0007] In order to achieve the above-mentioned invention object, the present invention adopts the following technical scheme:
[0008] A one-component bonding addition type organic silicone adhesive for an electronic controller unit, wherein the specific formula of the one-component bonding addition type organic silicone adhesive for an electronic controller unit is, in parts by weight:
[0009] 90~130 parts of vinyl-terminated silicone oil,
[0010] 5~15 parts of hydrogen silicone oil,
[0011] 0.3~3 parts of fumed silica,
[0012] 60~95 parts of modified nano boron nitride,
[0013] 15~35 parts of ultra-high functionality crosslinking agent,
[0014] Thickener 7~20 parts,
[0015] 20~45 parts of liquid flame retardant,
[0016] 0.5~2 parts of catalyst,
[0017] 0.1~0.5 parts of anti-poisoning agent,
[0018] Inhibitor 0.2~0.8 parts;
[0019] The number average molecular weight of the vinyl-terminated silicone oil is 6000-28000 g / mol, the viscosity at 25° C. is 100-1000 mPa·s, and the mass content of vinyl is 0.18-1 wt %;
[0020] The hydrogen-containing silicone oil has a number average molecular weight of 500-3000 g / mol, a viscosity of 10-500 mPa·s at 25° C., and a mass content of active hydrogen of 0.2-1.5 wt %;
[0021] The particle size of the fumed silica is 10-100 nm;
[0022] The liquid flame retardant is bisphenol A bis(diphenyl phosphate);
[0023] The catalyst is an isopropanol solution of chloroplatinic acid, wherein the mass concentration of chloroplatinic acid is 1-5wt%;
[0024] The anti-poisoning agent is aluminum isopropoxide;
[0025] The inhibitor is diethyl fumarate;
[0026] The following are further improvements to the above technical solution:
[0027] Step 1: Preparation of modified nano boron nitride
[0028] Add nano boron nitride and deionized water into a stirring kettle, control the stirring rate at 2000-4500 rpm, vigorously stir and disperse for 4-9 hours, then raise the temperature and keep the temperature constant at 40-65°C, reduce the stirring rate to 1000-1800 rpm, then add trifluoroacetic acid and peracetic acid, stir and react at the constant temperature for 1-2.5 hours, centrifuge, wash the obtained solid with anhydrous ethanol for 3-5 times, put it in a vacuum oven at 50-75°C and dry it for 3-7 hours to obtain surface-etched nano boron nitride, and then remove the surface-etched nano boron nitride. The etched nano boron nitride, toluene and sodium tridecyl sulfosuccinate are placed in a dispersion kettle, and the speed is controlled at 8000-12000 rpm. After strong dispersion for 5-9 hours, the dispersion speed is reduced to 2000-4500 rpm, and the temperature is raised and kept constant at 80-110°C. Trifluoropropyl trichlorosilane is added, and the reaction is carried out for 4-7 hours under condensation reflux state, and then centrifuged. The obtained solid is washed with anhydrous ethanol for 3-5 times, and then placed in a vacuum oven at 60-80°C and dried for 2-6 hours to obtain modified nano boron nitride.
[0029] The particle size of the nano boron nitride is 10-100 nm;
[0030] The mass ratio of the nano boron nitride, deionized water, trifluoroacetic acid and peracetic acid is 20-60:80-150:3-11:1-4;
[0031] The mass ratio of the surface-etched nano boron nitride, toluene, sodium ditridecyl sulfosuccinate, and trifluoropropyltrichlorosilane is 25-50:90-130:1-4:3-8.
[0032] Step 2: Preparation of ultra-high functionality cross-linking agent
[0033] Dissolve tannic acid in anhydrous ethanol, then heat and maintain the temperature at 60-85°C, control the stirring rate at 500-1000 rpm, add vinyltrimethoxysilane under stirring, condensation reflux, and then stir and react for 6-10 hours at a constant temperature, centrifuge, and vacuum dry the separated solid at 50-80°C for 4-7 hours to obtain an ultra-high functionality cross-linking agent;
[0034] The mass ratio of the tannic acid, anhydrous ethanol and vinyl trimethoxy silane is 15-45:130-190:5-9.
[0035] Step 3: Preparation of tackifier
[0036] Add diethanolamine and hydroxy-terminated vinyl silicone oil to a reaction kettle, evacuate the kettle to replace nitrogen, and then, under nitrogen protection, control the stirring rate to 500-950 rpm, raise the temperature and keep the temperature constant at 75-95° C., add isopropyl titanate, and then drop 3-(2,3-epoxypropoxy)propylmethyldiethoxysilane at a rate of 0.1-1 g / min. After the dropwise addition is completed, stir and react at a constant temperature for 6-10 hours, continue to maintain the constant temperature in the kettle, and evacuate and distill under reduced pressure for 1.5-3.5 hours, then add hexamethyldisilazane, continue to stir and react for 2-3.5 hours, cool to room temperature, discharge the material, and put it into a dry, oxygen-free sealed container for standby use, so as to obtain a tackifier;
[0037] The terminal hydroxyl vinyl silicone oil has a hydroxyl content of 5 to 8 mol / mol, a vinyl content of 6 to 8.5 mol / mol, and a viscosity of 30 to 300 mPa·s at 25° C.;
[0038] The feeding mass ratio of the diethanolamine, the terminal hydroxyl vinyl silicone oil, isopropyl titanate, 3-(2,3-epoxypropoxy)propylmethyldiethoxysilane and hexamethyldisilazane is 10-30:40-65:0.5-2:5-15:1-6.
[0039] Step 4: Preparation of addition type organic silicone adhesive
[0040] According to the specific formula of the one-component bonding addition type organic silicone adhesive for electronic controller units in parts by weight, vinyl-terminated silicone oil, hydrogen-containing silicone oil, liquid flame retardant, anti-poisoning agent, inhibitor, and fumed silica are placed in a dry double planetary mixer, evacuated and maintained in a vacuum state in the mixer, and the stirring rate is controlled at 100-130 rpm and the dispersion rate is 9500-12000 rpm. After continuous stirring and dispersion for 4-8 hours, modified nano boron nitride is added, and stirring and dispersion is continued for 5-10 hours. Then, an ultra-high functionality cross-linking agent, a tackifier, and a catalyst are added, and stirring and dispersion is continued for 3-7 hours to obtain a glue solution. After vacuum degassing, it is filled into a plastic finished product bottle, and sealed with nitrogen to obtain a one-component bonding addition type organic silicone adhesive for electronic controller units.
[0041] Compared with the prior art, the present invention achieves the following beneficial effects:
[0042] 1. The present invention uses a mixed acid solution of trifluoroacetic acid and peracetic acid to etch and modify the surface of nano-boron nitride, so that a large number of hydroxyl functional groups are generated on the surface of the nano-boron nitride. After these highly reactive hydroxyl functional groups react with trifluoropropyltrichlorosilane, the surface of the nano-boron nitride is transformed from a highly polar surface to a non-polar highly hydrophobic surface, and then the nano-boron nitride can be evenly dispersed in the organic silica gel liquid at the nanoscale, thus ensuring that the nano-boron nitride particles can form a thermally conductive network with good contact after the glue liquid is cured, thereby achieving high thermal conductivity performance;
[0043] 2. The present invention uses tannic acid and vinyl trimethoxysilane to react to generate an ultra-high functionality cross-linking agent. Tannic acid contains a large number of carboxyl groups. After these carboxyl groups react with trimethoxysilane in vinyl trimethoxysilane, the ends of tannic acid become highly hydrophobic vinyl functional groups. These vinyl functional groups are directly connected to silicon atoms, so they can also undergo addition reactions with hydrogen-containing silicone oil to produce ultra-high functionality cross-linking. This can not only improve the mechanical strength of the colloid obtained after the glue is cured, but also shorten the distance between nano boron nitride particles by increasing the cross-linking density, thereby playing a positive role in improving thermal conductivity;
[0044] 3. In the present invention, diethanolamine, hydroxyl-terminated vinyl silicone oil, and 3-(2,3-epoxypropoxy)propylmethyldiethoxysilane undergo polycondensation reaction under the catalytic action of isopropyl titanate, and then the residual hydroxyl groups are capped with hexamethyldisilazane, and finally a tackifier containing two polar functional groups, namely, secondary amine and epoxy, is generated. These polar functional groups can improve the adhesion to the surface of the substrate during the injection of the glue. In addition, after the hexamethyldisilazane is capped, the silicon-hydrogen bond formed has a very active hydrolysis reaction activity, and can also provide better wetting and bonding properties for the glue when it contacts the substrate;
[0045] 4. The one-component bonding addition type organic silicone adhesive for electronic controller units obtained by the present invention has a thermal conductivity of 7.53-7.85 W / (m·k), a bonding strength of 3.1-3.4 MPa, a tensile strength of 6.5-7.3 MPa, and a flame retardant grade of V0. DETAILED DESCRIPTION
[0046] The preferred embodiments of the present invention are described below. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0047] Example 1: A one-component bonding addition type silicone adhesive for electronic controller units
[0048] Step 1: Preparation of modified nano boron nitride
[0049] Add nano boron nitride and deionized water into a stirring kettle, control the stirring rate at 3500 rpm, vigorously stir and disperse for 8 hours, then heat and keep the temperature constant at 60°C, reduce the stirring rate to 1500 rpm, then add trifluoroacetic acid and peracetic acid, stir and react for 2 hours at constant temperature, centrifuge, wash the obtained solid with anhydrous ethanol for 4 times, put it in a vacuum oven at 70°C and dry it for 6 hours to obtain surface-etched nano boron nitride, then put the surface-etched nano boron nitride, toluene, and sodium tridecyl sulfosuccinate into a dispersion kettle, control the speed at 11000 rpm, vigorously disperse for 6 hours, reduce the dispersion rate to 4000 rpm, heat and keep the temperature constant at 100°C, add trifluoropropyl trichlorosilane, react for 5 hours under condensation reflux, centrifuge, wash the obtained solid with anhydrous ethanol for 4 times, put it in a vacuum oven at 75°C and dry it for 3 hours to obtain modified nano boron nitride;
[0050] The particle size of the nano boron nitride is 60nm;
[0051] The mass ratio of the nano boron nitride, deionized water, trifluoroacetic acid and peracetic acid is 45:120:8:3;
[0052] The mass ratio of the surface-etched nano-boron nitride, toluene, sodium ditridecyl sulfosuccinate, and trifluoropropyltrichlorosilane is 40:110:3:7.
[0053] Step 2: Preparation of ultra-high functionality cross-linking agent
[0054] Dissolve tannic acid in anhydrous ethanol, then heat and maintain constant temperature at 80°C, control stirring rate at 800 rpm, add vinyltrimethoxysilane under stirring condensation reflux, then stir and react at constant temperature for 9 hours, centrifuge, and vacuum dry the separated solid at 70°C for 5 hours to obtain an ultra-high functionality crosslinking agent;
[0055] The mass ratio of the tannic acid, anhydrous ethanol and vinyltrimethoxysilane is 40:170:8.
[0056] Step 3: Preparation of tackifier
[0057] Add diethanolamine and terminal hydroxyl vinyl silicone oil into a reaction kettle, evacuate the kettle to replace nitrogen, and then, under nitrogen protection, control the stirring rate to 700 rpm, raise the temperature and keep the temperature constant at 80°C, add isopropyl titanate, and then drop 3-(2,3-epoxypropoxy)propylmethyldiethoxysilane at a rate of 0.6 g / min. After the dropwise addition is completed, stir and react at a constant temperature for 9 hours, continue to maintain the constant temperature in the kettle, and evacuate and distill under reduced pressure for 2 hours, then add hexamethyldisilazane, continue to stir and react for 3 hours, cool to room temperature, discharge the material, and put it into a dry, oxygen-free sealed container for standby use, so as to obtain a tackifier;
[0058] The terminal hydroxyl vinyl silicone oil has a hydroxyl content of 6 mol / mol, a vinyl content of 7 mol / mol, and a viscosity of 120 mPa·s at 25° C.;
[0059] The feed mass ratio of the diethanolamine, the terminal hydroxyl vinyl silicone oil, isopropyl titanate, 3-(2,3-epoxypropoxy)propylmethyldiethoxysilane and hexamethyldisilazane is 22:55:1:9:3.
[0060] Step 4: Preparation of addition type silicone adhesive
[0061] The specific formula of the one-component bonding addition type organic silicone adhesive for the electronic controller unit is, in parts by weight:
[0062] 120 parts of vinyl-terminated silicone oil,
[0063] 11 parts of hydrogen silicone oil,
[0064] 0.9 parts of fumed silica,
[0065] 85 parts of modified nano boron nitride,
[0066] 20 parts of ultra-high functionality crosslinking agent,
[0067] Thickener 14 parts,
[0068] 29 parts of liquid flame retardant,
[0069] 1 part of catalyst,
[0070] 0.4 parts of anti-poisoning agent,
[0071] 0.5 part of inhibitor;
[0072] The number average molecular weight of the vinyl-terminated silicone oil is 8000 g / mol, the viscosity at 25° C. is 600 mPa·s, and the mass content of vinyl is 0.6 wt %;
[0073] The hydrogen-containing silicone oil has a number average molecular weight of 1000 g / mol, a viscosity of 200 mPa·s at 25° C., and a mass content of active hydrogen of 0.9 wt %;
[0074] The particle size of the fumed silica is 30 nm;
[0075] The liquid flame retardant is bisphenol A bis(diphenyl phosphate);
[0076] The catalyst is an isopropanol solution of chloroplatinic acid, wherein the mass concentration of chloroplatinic acid is 2wt%;
[0077] The anti-poisoning agent is aluminum isopropoxide;
[0078] The inhibitor is diethyl fumarate;
[0079] According to the specific formula of the one-component bonding addition type organic silicone adhesive for electronic controller units in parts by weight, vinyl-terminated silicone oil, hydrogen-containing silicone oil, liquid flame retardant, anti-poisoning agent, inhibitor, and fumed silica are placed in a dry double planetary mixer, evacuated and maintained in a vacuum state in the mixer, and the stirring rate is controlled at 110 rpm and the dispersion rate is 10,000 rpm. After continuous stirring and dispersion for 5 hours, modified nano boron nitride is added, and stirring and dispersion is continued for 8 hours. Then, an ultra-high functionality cross-linking agent, a tackifier, and a catalyst are added, and stirring and dispersion is continued for 4 hours to obtain a glue solution. After vacuum degassing, it is filled into a plastic finished product bottle, and sealed with nitrogen to obtain a one-component bonding addition type organic silicone adhesive for electronic controller units.
[0080] Example 2: A one-component bonding addition type silicone adhesive for electronic controller units
[0081] Step 1: Preparation of modified nano boron nitride
[0082] Add nano boron nitride and deionized water into a stirring kettle, control the stirring rate at 2000 rpm, vigorously stir and disperse for 4 hours, heat and keep constant temperature at 40°C, reduce the stirring rate to 1000 rpm, then add trifluoroacetic acid and peracetic acid, stir and react for 1 hour at constant temperature, centrifuge, wash the obtained solid with anhydrous ethanol for 3 times, put it in a vacuum oven at 50°C and dry it for 3 hours to obtain surface-etched nano boron nitride, then put the surface-etched nano boron nitride, toluene, and sodium tridecyl sulfosuccinate into a dispersion kettle, control the speed at 8000 rpm, vigorously disperse for 5 hours, reduce the dispersion rate to 2000 rpm, heat and keep constant temperature at 80°C, add trifluoropropyl trichlorosilane, react for 4 hours under condensation reflux, centrifuge, wash the obtained solid with anhydrous ethanol for 3 times, put it in a vacuum oven at 60°C and dry it for 2 hours to obtain modified nano boron nitride;
[0083] The particle size of the nano boron nitride is 10 nm;
[0084] The mass ratio of the nano boron nitride, deionized water, trifluoroacetic acid and peracetic acid is 20:80:3:1;
[0085] The mass ratio of the surface-etched nano-boron nitride, toluene, sodium ditridecyl sulfosuccinate, and trifluoropropyltrichlorosilane is 25:90:1:3.
[0086] Step 2: Preparation of ultra-high functionality cross-linking agent
[0087] Dissolve tannic acid in anhydrous ethanol, then heat and keep the temperature constant at 60°C, control the stirring rate to 500 rpm, add vinyltrimethoxysilane under stirring, condensation reflux, and then stir and react for 6 hours at a constant temperature, centrifuge, and vacuum dry the separated solid at 50°C for 4 hours to obtain an ultra-high functionality cross-linking agent;
[0088] The mass ratio of the tannic acid, anhydrous ethanol and vinyltrimethoxysilane is 15:130:5.
[0089] Step 3: Preparation of tackifier
[0090] Add diethanolamine and terminal hydroxyl vinyl silicone oil into a reaction kettle, evacuate the kettle to replace nitrogen, and then, under nitrogen protection, control the stirring rate to 500 rpm, raise the temperature and keep the temperature constant at 75°C, add isopropyl titanate, and then drop 3-(2,3-epoxypropoxy)propylmethyldiethoxysilane at a rate of 0.1 g / min. After the dropwise addition is completed, stir and react at a constant temperature for 6 hours, continue to maintain the constant temperature in the kettle, and evacuate and distill under reduced pressure for 1.5 hours, then add hexamethyldisilazane, continue to stir and react for 2 hours, cool to room temperature, discharge the material, and put it into a dry, oxygen-free sealed container for standby use, so as to obtain a tackifier;
[0091] The terminal hydroxyl vinyl silicone oil has a hydroxyl content of 5 mol / mol, a vinyl content of 6 mol / mol, and a viscosity of 30 mPa·s at 25°C;
[0092] The feed mass ratio of the diethanolamine, the terminal hydroxyl vinyl silicone oil, isopropyl titanate, 3-(2,3-epoxypropoxy)propylmethyldiethoxysilane and hexamethyldisilazane is 10:40:0.5:5:1.
[0093] Step 4: Preparation of addition type organic silicone adhesive
[0094] The specific formula of the one-component bonding addition type organic silicone adhesive for the electronic controller unit is, in parts by weight:
[0095] 90 parts of vinyl-terminated silicone oil,
[0096] 5 parts of hydrogen silicone oil,
[0097] 0.3 parts of fumed silica,
[0098] 60 parts of modified nano boron nitride,
[0099] 15 parts of ultra-high functionality crosslinking agent,
[0100] Thickener 7 parts,
[0101] 20 parts of liquid flame retardant,
[0102] 0.5 parts of catalyst,
[0103] 0.1 part of anti-poisoning agent,
[0104] Inhibitor 0.2 parts;
[0105] The number average molecular weight of the vinyl-terminated silicone oil is 6000 g / mol, the viscosity at 25° C. is 100 mPa·s, and the mass content of vinyl is 0.18 wt %;
[0106] The hydrogen-containing silicone oil has a number average molecular weight of 500 g / mol, a viscosity of 10 mPa·s at 25° C., and a mass content of active hydrogen of 0.2 wt %;
[0107] The particle size of the fumed silica is 10 nm;
[0108] The liquid flame retardant is bisphenol A bis(diphenyl phosphate);
[0109] The catalyst is an isopropanol solution of chloroplatinic acid, wherein the mass concentration of chloroplatinic acid is 1wt%;
[0110] The anti-poisoning agent is aluminum isopropoxide;
[0111] The inhibitor is diethyl fumarate;
[0112] According to the specific formula of the one-component bonding addition type organic silicone adhesive for electronic controller units in parts by weight, vinyl-terminated silicone oil, hydrogen-containing silicone oil, liquid flame retardant, anti-poisoning agent, inhibitor, and fumed silica are placed in a dry double planetary mixer, evacuated and maintained in a vacuum state in the mixer, and the stirring rate is controlled at 100 rpm and the dispersion rate is 9500 rpm. After continuous stirring and dispersion for 4 hours, modified nano boron nitride is added, and stirring and dispersion is continued for 5 hours. Then, an ultra-high functionality cross-linking agent, a tackifier, and a catalyst are added, and stirring and dispersion is continued for 3 hours to obtain a glue solution. After vacuum degassing, it is filled into a plastic finished product bottle, and sealed with nitrogen to obtain a one-component bonding addition type organic silicone adhesive for electronic controller units.
[0113] Example 3: A one-component bonding addition type silicone adhesive for electronic controller units
[0114] Step 1: Preparation of modified nano boron nitride
[0115] Add nano boron nitride and deionized water into a stirring kettle, control the stirring rate at 4500 rpm, vigorously stir and disperse for 9 hours, heat and keep constant temperature at 65°C, reduce the stirring rate to 1800 rpm, then add trifluoroacetic acid and peracetic acid, stir and react at constant temperature for 2.5 hours, centrifuge, wash the obtained solid with anhydrous ethanol for 5 times, put it in a vacuum oven at 75°C and dry it for 7 hours to obtain surface-etched nano boron nitride, then put the surface-etched nano boron nitride, toluene, sodium tridecyl sulfosuccinate into a dispersion kettle, control the speed at 12000 rpm, vigorously disperse for 9 hours, reduce the dispersion rate to 4500 rpm, heat and keep constant temperature at 110°C, add trifluoropropyl trichlorosilane, react for 7 hours under condensation reflux, centrifuge, wash the obtained solid with anhydrous ethanol for 5 times, put it in a vacuum oven at 80°C and dry it for 6 hours to obtain modified nano boron nitride;
[0116] The particle size of the nano boron nitride is 100 nm;
[0117] The mass ratio of the nano boron nitride, deionized water, trifluoroacetic acid and peracetic acid is 60:150:11:4;
[0118] The mass ratio of the surface-etched nano-boron nitride, toluene, sodium ditridecyl sulfosuccinate, and trifluoropropyltrichlorosilane is 50:130:4:8.
[0119] Step 2: Preparation of ultra-high functionality cross-linking agent
[0120] Dissolve tannic acid in anhydrous ethanol, then heat and maintain the temperature at 85°C, control the stirring rate at 1000 rpm, add vinyltrimethoxysilane under stirring, condensation reflux, and then stir and react for 10 hours at a constant temperature, centrifuge, and vacuum dry the separated solid at 80°C for 7 hours to obtain an ultra-high functionality cross-linking agent;
[0121] The mass ratio of the tannic acid, anhydrous ethanol and vinyl trimethoxysilane is 45:190:9.
[0122] Step 3: Preparation of tackifier
[0123] Add diethanolamine and terminal hydroxyl vinyl silicone oil into a reaction kettle, evacuate the kettle to replace nitrogen, and then, under nitrogen protection, control the stirring rate to 950 rpm, raise the temperature and keep it constant at 95°C, add isopropyl titanate, and then drop 3-(2,3-epoxypropoxy)propylmethyldiethoxysilane at a rate of 1 g / min. After the dropwise addition is completed, stir and react at a constant temperature for 10 hours, continue to maintain the constant temperature in the kettle, and evacuate and distill under reduced pressure for 3.5 hours, then add hexamethyldisilazane, continue to stir and react for 3.5 hours, cool to room temperature, discharge the material, and put it into a dry, oxygen-free sealed container for standby use, so as to obtain a tackifier;
[0124] The terminal hydroxyl vinyl silicone oil has a hydroxyl content of 8 mol / mol, a vinyl content of 8.5 mol / mol, and a viscosity of 300 mPa·s at 25° C.;
[0125] The feed mass ratio of the diethanolamine, the terminal hydroxyl vinyl silicone oil, isopropyl titanate, 3-(2,3-epoxypropoxy)propylmethyldiethoxysilane and hexamethyldisilazane is 30:65:2:15:6.
[0126] Step 4: Preparation of addition type silicone adhesive
[0127] The specific formula of the one-component bonding addition type organic silicone adhesive for the electronic controller unit is, in parts by weight:
[0128] 130 parts of vinyl-terminated silicone oil,
[0129] 15 parts of hydrogen silicone oil,
[0130] 3 parts of fumed silica,
[0131] 95 parts of modified nano boron nitride,
[0132] 35 parts of ultra-high functionality crosslinking agent,
[0133] 20 parts of tackifier,
[0134] 45 parts of liquid flame retardant,
[0135] 2 parts of catalyst,
[0136] 0.5 parts of anti-poisoning agent,
[0137] Inhibitor 0.8 parts;
[0138] The number average molecular weight of the vinyl-terminated silicone oil is 28000 g / mol, the viscosity at 25° C. is 1000 mPa·s, and the mass content of vinyl is 1 wt %;
[0139] The hydrogen-containing silicone oil has a number average molecular weight of 3000 g / mol, a viscosity of 500 mPa·s at 25° C., and a mass content of active hydrogen of 1.5 wt %;
[0140] The particle size of the fumed silica is 100 nm;
[0141] The liquid flame retardant is bisphenol A bis(diphenyl phosphate);
[0142] The catalyst is an isopropanol solution of chloroplatinic acid, wherein the mass concentration of chloroplatinic acid is 5wt%;
[0143] The anti-poisoning agent is aluminum isopropoxide;
[0144] The inhibitor is diethyl fumarate;
[0145] According to the specific formula of the one-component bonding addition type organic silicone adhesive for electronic controller units in parts by weight, vinyl-terminated silicone oil, hydrogen-containing silicone oil, liquid flame retardant, anti-poisoning agent, inhibitor, and fumed silica are placed in a dry double planetary mixer, evacuated and maintained in a vacuum state in the mixer, and the stirring rate is controlled at 130 rpm and the dispersion rate is 12000 rpm. After continuous stirring and dispersion for 8 hours, modified nano boron nitride is added, and stirring and dispersion is continued for 10 hours. Then, an ultra-high functionality cross-linking agent, a tackifier, and a catalyst are added, and stirring and dispersion is continued for 7 hours to obtain a glue solution. After vacuum degassing, it is filled into a plastic finished product bottle, and sealed with nitrogen to obtain a one-component bonding addition type organic silicone adhesive for electronic controller units.
[0146] Comparative Example 1: Based on Example 1, step 1, preparation of modified nano-boron nitride, is not performed. In step 4, preparation of addition-type organic silicone adhesive, 85 parts of modified nano-boron nitride are replaced with 85 parts of nano-boron nitride. The specific operation is as follows:
[0147] Step 1, preparation of modified nano boron nitride is not performed;
[0148] The operations of steps 2 and 3 are the same as those of Example 1;
[0149] Step 4: Preparation of addition type silicone adhesive
[0150] 85 parts of modified nano-boron nitride were replaced by 85 parts of nano-boron nitride, and the other operations were the same as in Example 1.
[0151] Comparative Example 2: Based on Example 1, step 2, preparation of ultra-high functionality cross-linking agent, is not performed. In step 4, preparation of addition-type organic silicone adhesive, 20 parts of ultra-high functionality cross-linking agent are replaced by 20 parts of vinyl-terminated silicone oil in equal amounts. The specific operation is as follows:
[0152] The operation of step 1 is the same as that of embodiment 1;
[0153] Step 2, preparation of ultra-high functionality cross-linking agent is not performed;
[0154] The operation of step 3 is the same as that of embodiment 1;
[0155] Step 4: Preparation of addition type silicone adhesive
[0156] The 20 parts of ultra-high functionality cross-linking agent were replaced by 20 parts of vinyl-terminated silicone oil, and the other operations were the same as in Example 1.
[0157] Comparative Example 3: Based on Example 1, step 3, preparation of tackifier, is not performed. In step 4, preparation of addition-type organic silicone adhesive, 14 parts of tackifier are replaced by 14 parts of vinyl-terminated silicone oil. The specific operation is as follows:
[0158] The operations of steps 1 and 2 are the same as those of Example 1;
[0159] Step 3, preparation of tackifier is not performed;
[0160] Step 4: Preparation of addition type silicone adhesive
[0161] The 14 parts of tackifier were replaced by 14 parts of vinyl-terminated silicone oil, and the other operations were the same as in Example 1.
[0162] Performance Test:
[0163] The one-component bonding addition type organic silicone adhesive for electronic controller units obtained in Examples 1, 2, 3 and Comparative Examples 1, 2, 3 was mixed evenly with component A and component B in a mass ratio of 2:1 and then glued. The following performance tests were performed on the gluing process and the obtained glue layer:
[0164] 1. Thermal conductivity: Tested in accordance with ASTM D5470-2012;
[0165] 2. Adhesion performance: Tested in accordance with GB / T 11211-2009;
[0166] 3. Tensile strength: Tested in accordance with GB / T528-2009;
[0167] 4. Flame retardant performance: tested in accordance with the US ANSI / UL-94-1985 standard;
[0168] The specific test results are shown in Table 1:
[0169] Table 1
[0170]
[0171] From the data in Table 1, it can be seen that in Comparative Example 1 where nano boron nitride is not modified, the thermal conductivity is reduced to the lowest value among all embodiments and comparative examples, the bonding strength is also reduced to half of that of Example 1, and the tensile strength is greatly reduced, which shows that if nano boron nitride is not surface modified, it is difficult to obtain nanoscale dispersion in the organic silica gel liquid, which leads to a significant reduction in various properties of the colloid after curing; in Comparative Example 2 where no ultra-high functionality cross-linking agent is added, the thermal conductivity is significantly reduced, the bonding strength is also significantly reduced, and the tensile strength is significantly reduced, which shows that the ultra-high functionality cross-linking agent has a great influence on the mechanical properties of the colloid after curing, and can affect the thermal conductivity of the colloid after curing by affecting the cross-linking density; in Comparative Example 3 where no tackifier is added, the thermal conductivity is reduced, the bonding strength decreases most dramatically, and the tensile strength is also significantly reduced, which shows that the tackifier can effectively improve the adhesion to the substrate surface during the curing process of the glue liquid, and also affects the overall tensile strength and thermal conductivity of the glue layer after the glue liquid is cured.
[0172] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A one-component bonding addition type organic silicone adhesive for electronic controller units, characterized in that: The specific formula of the one-component bonding addition type organic silicone adhesive for the electronic controller unit is, in parts by weight: 90~130 parts of vinyl-terminated silicone oil, 5~15 parts of hydrogen silicone oil, 0.3~3 parts of fumed silica, 60~95 parts of modified nano boron nitride, 15~35 parts of ultra-high functionality crosslinking agent, Thickener 7~20 parts, 20~45 parts of liquid flame retardant, 0.5~2 parts of catalyst, 0.1~0.5 parts of anti-poisoning agent, Inhibitor 0.2~0.8 parts; The number average molecular weight of the vinyl-terminated silicone oil is 6000-28000 g / mol, the viscosity at 25° C. is 100-1000 mPa·s, and the mass content of vinyl is 0.18-1 wt %; The hydrogen-containing silicone oil has a number average molecular weight of 500-3000 g / mol, a viscosity of 10-500 mPa·s at 25° C., and a mass content of active hydrogen of 0.2-1.5 wt %; The particle size of the fumed silica is 10-100 nm; The liquid flame retardant is bisphenol A bis(diphenyl phosphate); The catalyst is an isopropanol solution of chloroplatinic acid, wherein the mass concentration of chloroplatinic acid is 1-5wt%; The anti-poisoning agent is aluminum isopropoxide; The inhibitor is diethyl fumarate; The modified nano boron nitride is prepared by adding nano boron nitride and deionized water into a stirring kettle, controlling the stirring rate to 2000-4500 rpm, vigorously stirring and dispersing for 4-9 hours, heating and maintaining the temperature at 40-65°C, reducing the stirring rate to 1000-1800 rpm, then adding trifluoroacetic acid and peracetic acid, stirring and reacting at the constant temperature for 1-2.5 hours, centrifuging, washing the obtained solid with anhydrous ethanol for 3-5 times, and drying it in a vacuum oven at 50-75°C for 3-7 hours to obtain a surface-etched nano boron nitride. Boron, then put the surface-etched nano boron nitride, toluene, and sodium tridecyl sulfosuccinate into a dispersion kettle, control the speed at 8000-12000 rpm, disperse vigorously for 5-9 hours, reduce the dispersion speed to 2000-4500 rpm, heat and keep the temperature at 80-110°C, add trifluoropropyl trichlorosilane, react for 4-7 hours under condensation reflux, centrifuge, wash the obtained solid with anhydrous ethanol for 3-5 times, put it in a vacuum oven at 60-80°C and dry it for 2-6 hours to obtain modified nano boron nitride; The ultra-high functionality cross-linking agent is prepared by: dissolving tannic acid in anhydrous ethanol, then heating and maintaining the temperature at 60-85°C, controlling the stirring rate to 500-1000 rpm, adding vinyl trimethoxy silane under stirring, condensing and reflux, and then stirring and reacting at a constant temperature for 6-10 hours, centrifuging, and vacuum drying the separated solid at 50-80°C for 4-7 hours to obtain the ultra-high functionality cross-linking agent; The preparation method of the tackifier is as follows: adding diethanolamine and terminal hydroxyl vinyl silicone oil into a reaction kettle, evacuating the kettle to replace nitrogen, then controlling the stirring rate to 500-950 rpm under nitrogen protection, heating and keeping the temperature constant at 75-95°C, adding isopropyl titanate, then dripping 3-(2,3-epoxypropoxy)propylmethyldiethoxysilane at a rate of 0.1-1 g / min, stirring and reacting at a constant temperature for 6-10 hours after the dropwise addition, continuing to maintain the constant temperature in the kettle, evacuating the kettle to perform reduced pressure distillation for 1.5-3.5 hours, then adding hexamethyldisilazane, continuing to stir and react for 2-3.5 hours, cooling to room temperature, discharging the material, and placing it in a dry, oxygen-free sealed container for standby use, thereby obtaining the tackifier; The terminal hydroxyl vinyl silicone oil has a hydroxyl content of 5 to 8 mol / mol, a vinyl content of 6 to 8.5 mol / mol, and a viscosity of 30 to 300 mPa·s at 25° C.; The particle size of the nano boron nitride is 10-100 nm; The mass ratio of the nano boron nitride, deionized water, trifluoroacetic acid and peracetic acid is 20-60:80-150:3-11:1-4; The mass ratio of the surface-etched nano-boron nitride, toluene, sodium ditridecyl sulfosuccinate, and trifluoropropyltrichlorosilane is 25-50:90-130:1-4:3-8; The mass ratio of the tannic acid, anhydrous ethanol and vinyl trimethoxy silane is 15-45:130-190:5-9; The feeding mass ratio of the diethanolamine, the terminal hydroxyl vinyl silicone oil, isopropyl titanate, 3-(2,3-epoxypropoxy)propylmethyldiethoxysilane and hexamethyldisilazane is 10-30:40-65:0.5-2:5-15:1-6.
2. The one-component bonding addition type organic silicone adhesive for electronic controller units according to claim 1, characterized in that: The one-component bonding addition type organic silicone adhesive for electronic controller units has a preparation method as follows: according to the specific formula of the one-component bonding addition type organic silicone adhesive for electronic controller units in parts by weight, vinyl-terminated silicone oil, hydrogen-containing silicone oil, liquid flame retardant, anti-poisoning agent, inhibitor, and gas-phase silica are placed in a dry double planetary mixer, vacuuming and maintaining the vacuum state in the mixer, controlling the stirring rate to 100-130 rpm and the dispersion rate to 9500-12000 rpm, stirring and dispersing continuously for 4-8 hours, then adding modified nano boron nitride, stirring and dispersing continuously for 5-10 hours, then adding an ultra-high functionality cross-linking agent, a tackifier, and a catalyst, stirring and dispersing continuously for 3-7 hours, obtaining a glue solution, vacuum degassing, filling into a plastic finished product bottle, and sealing with nitrogen to obtain the one-component bonding addition type organic silicone adhesive for electronic controller units.
Citation Information
Patent Citations
Heat-resistant single-component addition type organosilicone adhesive and preparation method thereof
CN111154453A
Preparation method of single-component addition type liquid silicone rubber
CN116622243A
Single component addition type organic silicon flame retardant bonding glue and preparation method thereof
CN110128999A
Organic-Inorganic Composite Adhesive for Backsheets In Photovoltaic Modules
KR1020150118595A